Detection of virus-specific immunoglobulins using a doubly labeled fluorescein-125I antibody. - Parkinson, A J (1976)
Commercially prepared fluorescein-labeled antihuman antibodies were labed with 125I and used to compre specific herpes simplex virus antibody titers as determined by indirect fluorescent antibody and radioimmunoassay techniques. Total virus-specific immunoglobulin and virus-specific immunoglobulin G titers did not vary by more than one twofold dilution when compared by the two methods.